Binary and ternary complexes of epinephrine with alginate and biologically and environmentally relevant metal cations - Irto, Anna; Cigala, Rosalia Maria; Alessandrello, Chiara; De Stefano, Concetta; Gattuso, Giuseppe; Crea, Francesco (Frontiers in Chemistry, 2023)
The speciation of epinephrine (Eph-) in the presence of alginate (Alg2-) and two biological and environmental relevant metal cations (Cu2+, UO22+), was investigated at T = 298.15K, I = 0.15-1.00 mol dm-3 in NaCl(aq). The formation of binary and ternary complexes was evaluated and, since epinephrine can behave as a zwitterion, the Eph-/Alg2- interaction was studied by means of DOSY NMR. The dependence of the equilibrium constants on ionic strength was studied using an extended Debye-Hückel type equation and the SIT approach. The effect of temperature was investigated by means of isoperibolic titration calorimetry: the entropic contribution resulted the driving force for the Cu2+/Eph- complexes formation. The sequestering ability of Eph- and Alg2- on Cu2+, evaluated by the pL0.5 calculation, increases with pH and ionic strength. The determination of pM parameter showed that Eph- has a higher Cu2+ affinity with respect to Alg2-. The formation of Eph-/Alg2- species was also investigated by UV-Vis spectrophotometry and 1H NMR measurements. The ternary Cu2+/Eph-/Alg2- and Cu2+/UO22+/Eph- interactions were also studied. The “extra-stability” calculated for the mixed ternary species confirmed that their formation is thermodynamically favorable.